Tensile mechanical properties and surface chemical sensitivity of technical fibres from date palm fruit branches (Phoenix dactylifera L.) - Amroune, Salah (Université de M'sila, 2015)
The paper describes the manufacturing process and the characterization of the tensile mechanical properties of treated and untreated palm dates long technical fibres. The fibres extracted from Fruit Bunch Branch of Palm Date (FBBPD) have been subjected to alkaline treatment with different NaOH concentrations at room temperature. The experimental results show that the chemical technical fibre treatments provide an increase of the mechanical properties (tensile strength and Young’s modulus) under quasistatic tensile loading. A specific treatment leads a threefold increase of the failure stress. An analysis of stress at failure has been performed over a population of 630 samples using Weibull statistics with two and three-parameters, together with a one-way analysis of variance (ANOVA). FBBPD technical fibres show stiffness and strength performance comparable to the ones of agave Americana L fibres, and higher failure at strength than okra fibres.
Keywords: A. Wood B. Mechanical properties C. Statistical properties/methods D. Optical microscopy